Diabetic retinopathy management guidelines. (October 2012) - Chakrabarti, Rahul; Harper, C Alex; Keeffe, Jill Elizabeth
Diabetic retinopathy (DR) is an important cause of avoidable blindness worldwide. Seventy percent of diabetes occur in low and lower-middle income countries. Clinical practice guidelines for the management of DR have been implemented throughout the world, but mainly in developed nations. However, there is considerable variation between existing guidelines in the recommended frequency of referral, methods for examination and personnel involved in screening and review. This review compares the differences between current available guidelines in the context of the current medical evidence and also addresses the implications for management of DR in countries with limited resources.